Monetary Variables and their Relationship to the Iraqi Stock Exchange Index - Alaa Abbas Dakhi (a), Dr. Abdul Hussein Jalil Abdulhasan(b), Dr. Hanaa Saad Mohammed (c) (Scholars Digest Publishing, 2023)
Financial markets are of great interest to developed and developing countries alike, because of their great role in mobilizing savings and directing them to various investment channels that support the growth and development of the economy, and these markets affect and are affected by many variables and economic policies, including It includes the monetary policy variables, and the research aimed to show the monetary policy variables in Iraq, which are represented by the money supply, interest rate, exchange rate and their relationship to the Iraq Stock Exchange Index.
Keywords: Monetary variables ،stock market index.